Specialization in Navigational Models - Fons, Joan (2002)
Nowadays, web applications have evolved into complex software systems where a large number of potential users can accede. Considering navigation as one of the emergent features of web applications, it is necessary to treat it in an adequate way providing the mechanisms to allow for reusing navigational specifications. This paper presents an 00 approach to capture properly the navigational semantics in order to use the navigational specialization as a tool for extending and reusing navigation characteristics and requirements.